Imaging cellular structures of atherosclerotic coronary arteries using circumferentially scanning micro-optical coherence tomography fiber probe ex vivo - Luo, Yuemei (2018)
Development and progression of coronary atherosclerotic lesions is mediated by a number of cellular components that are not readily visualized using the current clinical investigation tools. Visualizing these cellular components in situ and in vivo may allow early detection of the vulnerable plaques, with implications for coronary artery disease therapy and for the prevention of acute myocardial infarction. In this paper, we have developed a fiber-optic micro-optical coherence tomography ( μ OCT) probe for intravascular use. We conducted ex vivo imaging experiments in normal swine aorta and human atherosclerotic coronary arteries and demonstrated that the fiber-probe-based μ OCT could delineate not only the layered structures of arterial wall but also the cellular-level anatomical structures of atherosclerotic plaques, including foam cells and smooth muscle cells. These results demonstrate the feasibility of intravascular μ OCT imaging.